KONSEP ULUMUL QUR’AN SEBAGAI ILMU PENGETAHUAN AL-QUR’AN: 1. Ulumul Qur’an :, 2. Ulumul Qur’an Sebagai Ilmu dan Displin Ilmu - HASNA NURUL AZIZAH; KHUSNUL KHOTIMAH (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2024)
This article exists as a tool or reading to develop Islamic knowledge, especially the sciences contained in the Qur'an. Where the Al-Qur'an is the main source of basic legal sources used by Muslims in the various problems they face. To understand the Qur'an, various knowledge is needed, including "Ulumul Al-Qur'an". This knowledge includes discussions related to the Al-Qur'an in terms of the cause of its revelation, collection and sequence, knowledge of the verses makkiyah and madaniyyah, nasikh and mansukh and so on. The Ulumul Qur'an with its various branches and types was not born all at once, but through a process and development that can be divided into the transmission phase and the codification phase. For this article, the discussion will focus more on understanding the concept of Ulumul Qur'an as a science and discipline of Al-Quran knowledge, scope and branches of knowledge.